Social Media in Emergent Brazil How the Internet Affects Social Change - Spyer, Juliano (UCL Press, 2017)
Since the popularisation of the internet, low-income Brazilians have received little government support to help them access it. In response, they have largely self-financed their digital migration. Internet cafés became prosperous businesses in working-class neighbourhoods and rural settlements, and, more recently, families have aspired to buy their own home computer with hire purchase agreements. As low-income Brazilians began to access popular social media sites in the mid-2000s, affluent Brazilians ridiculed their limited technological skills, different tastes and poor schooling, but this did not deter them from expanding their online presence. Young people created profiles for barely literate older relatives and taught them to navigate platforms such as Facebook and WhatsApp. Based on 15 months of ethnographic research, this book aims to understand why low-income Brazilians have invested so much of their time and money in learning about social media. Juliano Spyer explores this question from a number of perspectives, including education, relationships, work and politics. He argues that social media is the way for low-income Brazilians to stay connected to the family and friends they see in person on a regular basis, which suggests that social media serves a crucial function in strengthening traditional social relations